IDENTIFICAÇÃO DE MARCADOR RAPD E SCAR RELACIONADOS AO CARACTERE FLORESCIMENTO PRECOCE EM Eucalyptus grandis1 - Domingues, Douglas Silva [UNESP]; Farro, Ana Paula Cazerta [UNESP]; Coscrato, Virgínia Elias [UNESP]; Mello, Eduardo José De; Oda, Shinitiro; Marino, Celso Luís [UNESP] (Universidade Federal de Santa Maria, 2006)
There are few available tools in eucalyptus breeding to accelerate the selection of superior genotypes, and one of the main tools to improve this process is the use of molecular markers linked to traits of interest. Using “Bulked Segregant Analysis”, we evaluated 81 RAPD molecular markers in a Eucalyptus grandis W. Hill ex Maiden progeny that segregates for early flowering, and one marker was identified as related to this trait. This RAPD marker was converted into a Sequence-Characterized Amplified Region (SCAR), which was then evaluated in a F1 progeny, and validated in other progenies that presents this trait. The SCAR marker was informative in the progeny in which one of the parental was the donor of the band, with an efficiency of 60%. These results describe the first SCAR marker developed for eucalypt and confirm this technique as a useful molecular tool for forestry breeding which could be employed to locate markers linked to other silvicultural traits.

No melhoramento genético de eucalipto, existem ainda poucos instrumentos disponíveis para acelerar a seleção de genótipos superiores, e uma das principais estratégias sugeridas para se acelerar este processo é a identificação de marcadores moleculares ligados a caracteres de interesse. Foram avaliados 81 marcadores RAPD em uma progênie F1 de Eucalyptus grandis W. Hill ex Maiden segregante para o caractere florescimento precoce utilizando-se a técnica de Bulked Segregant Analysis (BSA). Dentre esses marcadores, um se mostrou relacionado ao caractere, sendo então convertido em Sequence Characterized Amplified Region (SCAR), avaliado em cada indivíduo da progênie e validado em outras progênies que apresentam o caractere. O SCAR mostrou-se informativo na progênie que apresenta um dos parentais como doador do fragmento polimórfico, com eficiência de 60%. Esses resultados descrevem o primeiro marcador SCAR desenvolvido para eucalipto e confirmam a utilidade da técnica de BSA como ferramenta molecular no melhoramento genético florestal e que poderia ser empregada para localização de marcadores ligados a diferentes caracteres silviculturais.
IDENTIFICATION OF RAPD AND SCAR MARKER RELATED TO EARLY FLOWERING IN Eucalyptus grandis
Keywords: Bulked Segregant Analysis (BSA); early flowering, Eucalyptus, Sequence Characterized Amplified Region (SCAR); Bulked Segregant Analysis (BSA); Eucalyptus; florescimento precoce; Sequence Characterized Amplified Region (SCAR)